Applying Fiber Bragg Grating for Acoustic Sensor - Pakdeevanich, Paradorn; Likittananan, Nattapon; Promsen, Worrapass (Communications in Physics, 2019)
In this work, we interested to utilize Fiber Bragg Grating (FBG) for monitoring sound intensity level. Acoustic disturbance could induce strain and changing the refractive index of FBG. Therefore, light will interfere for the trough of transmission at one specific wavelength satisfied Bragg’s condition. In our demonstrations, FBG sensor was perturbed with sound intensity levels of 60, 80 and 100 dB , the measuring Bragg wavelength were recorded at 1552 nm, 1553 nm and 1555 nm, respectively. It was found that the Bragg wavelength shift has a quite linear variation with sound intensity level. In addition, the sensitivity for sensor was 0.0566 nm/dB. The obtained results are promising for developing acoustic and vibration sensors